TM6SF2 rs58542926 impacts lipid processing in liver and small intestine - O’Hare, Elizabeth A. (Hepatology, 2017)
The transmembrane 6 superfamily member 2 (TM6SF2) loss-of-function variant, rs58542926, is a genetic risk factor for nonalcoholic fatty liver disease and progression to fibrosis, but is paradoxically associated with lower levels of hepatic-derived triglyceride-rich lipoproteins (TRLs). TM6SF2 is expressed predominately in liver and small intestine, sites for triglyceride rich lipoprotein biogenesis and export. In light of this, we hypothesized that TM6SF2 may exhibit analogous effects on both liver and intestine lipid homeostasis. To test this, we genotyped rs58542926 in 983 bariatric surgery patients from the Geisinger Medical Center for Nutrition and Weight Management, Geisinger Health System (GHS) in PA and from 3,556 study participants enrolled in the Amish Complex Disease Research Program (ACDRP). Although these two cohorts have different metabolic profiles, carriers in both cohorts had improved fasting lipid profiles. Importantly, following a high fat challenge, carriers in the ACDRP cohort exhibited significantly lower postprandial serum triglycerides suggestive of a role for TM6SF2 in the small intestine. To gain further insight into this putative role, effects of TM6SF2 deficiency were studied in a zebrafish model and in cultured human Caco-2 enterocytes. In both systems TM6SF2-deficiency resulted in defects in small intestine metabolism in response to dietary lipids including significantly increased lipid accumulation, decreased lipid clearance and increased endoplasmic reticulum stress. Conclusions: These data strongly support a role of TM6SF2 in regulation of postprandial lipemia potentially through a similar function for TM6SF2 in the lipidation and/or export of both hepatically- and intestinally-derived TRLs.